The Role of Local Government in Enforcing Legal Regulations on the Transfer of Land Rights - Indriasari, Evy (Jurnal Pembaharuan Hukum, 2025)
This study aims to analyze the impact of the domicile requirement on the transfer of rights for rice fields protected by public regulations in Indonesia, with a focus on the challenges it creates for land market efficiency and agricultural sustainability. Using a qualitative approach with a literature review, the research explores existing legal frameworks, regulatory constraints, and their effects on land transactions. The findings reveal that the domicile requirement restricts access to the land market, excluding financially capable buyers who could manage agricultural land sustainably. The study suggests that expanding the eligibility criteria to include buyers within the same district, rather than limiting them to the same subdistrict, would enhance market efficiency and ensure more effective land management. The proposed policy change would allow for a broader pool of buyers while maintaining local oversight, thus contributing to the protection and sustainable management of rice fields. This research provides valuable insights for policymakers seeking to improve land use regulations and agricultural land management in Indonesia.